Core training still promises more than it can keep - Gøran Paulsen; Lars Haugvad; Paul Solberg (Fysioterapeuten, 2023)
Introduction: This is a rebuttal to «Comment to: Core training promises more than it can hold: A review of current literature and practical experience», by Sæterbakken and Andersen.